HF free greener Cl‐terminated MXene as novel electrocatalyst for overall water splitting in alkaline media. (31st March 2022) - Sarfraz, Bilal; Mehran, Muhammad Taqi; Baig, Mutawara Mahmood; Naqvi, Salman Raza; Khoja, Asif Hussain; Shahzad, Faisal
Summary: Hydrogen and oxygen evolution through electrochemical water splitting is essential for effective and inexpensive production of hydrogen and oxygen, which depends on the development of economical, and extremely active electrocatalysts. Two‐dimensional (2D) nano‐laminated materials are imperious as electrocatalysts due to their phenomenal properties and extensive scope of applications. In this work, we report a greener way of synthesizing MXene without hydrofluoric acid (HF) treatment and demonstrated its excellent electrochemical characteristics as an overall water‐splitting catalyst. Cl‐terminated MXenes (Ti3 C2 Cl2 ) were synthesized via a molten salt approach, in which the MAX phase (Ti3 AlC2 ) was reacted with copper chloride (CuCl2 ) salt followed by thermal treatment at a temperature of 550°C for 5 hours. The resulting Cl‐terminated MXene was characterized by scanning electron microscopy, X‐ray diffraction, transmission electron microscope, Raman, Fourier transform infrared spectroscopy, energy dispersive X‐ray analysis, X‐ray photoelectron spectroscopy, and electrochemical testing was performed in the alkaline media for oxygen evolution reactions (OER) and hydrogen evolution reactions (HER). For OER in 1 M KOH, Cl‐terminated MXene achieves a benchmark of 30 mA cm −2 current density at an overpotential of 330 mV and a Tafel slope of 48 mV dec −1, while HF‐MXene exhibits an overpotential of 390 mV and a Tafel slope of 136 mV dec −1 . For HER, Cl‐MXene attains an overpotential of 259 mV, and a Tafel slope of 92 mV dec −1 to achieve the 10 mA cm −2 current density, on the other hand, HF‐MXene achieves an overpotential of 444 mV and a Tafel slope of 311 mV dec −1 . Furthermore, the electrocatalyst exhibited excellent long‐term stability of 0.7 V at 100 mA cm −2 current density for 36 hours. The synthesis methodology for greener Cl‐terminated MXene coupled with an outstanding electrocatalytic activity is set to open new avenues of catalyst design for water splitting. Abstract : Cl‐MXene successfully synthesized by greener route via molten salt method. Cl‐MXene synthesized electrocatalyst demonstrated enhanced OER and HER performances as compared to traditional HF‐MXenes. The improved overall electrochemical activity is credited to the interface engineering of MXenes.